Status of Crop and Livestock Insurance Schemes in Punjab - Mohapatra, Lopamudra; Dhaliwal, R.K.; Dhaliwal, H.S (Indian Journal of Extension Education, 2010)
Status is the prevailing position of Crop and Livestock Insurance Schemes in Punjab which was measured with respect to different aspects such as type of farmers covered under these schemes, subsidy provided, type of crops and animals covered, premium etc. The major private players for Crop Insurance in Punjab were IFFCO-TOKIO General Insurance Company and ICICI Lombard. About 15.83 per cent of the respondents had availed the Crop Insurance Scheme; While 59.17 per cent of the respondents have availed the Livestock Insurance Scheme. About 96.67 per cent of the respondents had insured their crop from IFFC - TOKIO General Insurance Company (ITGI). Cooperative bank was the service provider for all the respondents availing Livestock Insurance and 96. 67 per cent of the respondents were provided with the Crop Insurance and Personal Insurance by the IFFCO. All the respondents were satisfied with the premium rate for the Livestock Insurance schemes and majority of the respondents availed the three year policy for the livestock.